Systematic Literature Review: Application of Whole Language Approach to Improve Indonesian Language Learning Outcomes of Elementary School Students - Safira, Ansella; Firmansah, Deri; Afriyadi, Muhammad Muchsin (Indo-MathEdu Intellectuals Journal, 2025)
The Whole Language approach has been widely applied in Indonesian language learning, but there is still a gap in understanding its effectiveness, especially in elementary schools. This study aims to examine the application and effectiveness of Whole Language in improving Indonesian learning outcomes in elementary school students. This study uses Systematic Literature Review (SLR). The article selection process was carried out through searches in indexed journal databases such as Google Scholar, DOAJ, and Garuda with the keywords "Whole Language", "Indonesian Language Learning", and "Elementary School Learning Outcomes" in the range from 2020 to 2025. Articles selected based on inclusion and exclusion criteria amounted to 20 articles that were analyzed in depth. The results of the analysis showed that the application of the Whole Language approach significantly improved the reading and writing skills of elementary school students. In addition, the application of this method also shows an increase in students' motivation to learn, which is reflected in their active involvement in reading and writing activities